(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article highlights the importance of using organo-mineral composts to improve the efficiency of cotton cultivation in saline soils. Due to their poor agrotechnical properties, saline lands have a negative impact on the yield of agricultural crops, particularly cotton. During the study, composts prepared from various organic materials (manure, glauconite agro-ore, and licorice waste) were tested. Their effects on cotton growth, development, and final yield were analyzed. The results showed that the use of organo-mineral composts had a positive impact on reducing soil salinity, improving the agrochemical properties of the soil, and increasing cotton productivity. Notably, the application of 22 tons of organo-mineral compost containing a mixture of 16 tons of manure, 3 tons of glauconite, and 3 tons of licorice waste significantly optimized the cotton vegetation period and considerably improved both the quality and quantity of the yield. The article also discusses the ecological and economic advantages of this method. The findings of the study serve as a scientific and practical basis for establishing sustainable agriculture in saline-prone regions.